Breast, cervical, and colorectal cancer screening rates amongst female Cambodian, Somali, and Vietnamese immigrants in the USA - Fielding Susan J; James Nathaniel W; Pringle Jane P; Samuel Ponnila S; Fairfield Kathleen M (BMC, 2009)
Abstract Introduction Minority women, particularly immigrants, have lower cancer screening rates than Caucasian women, but little else is known about cancer screening among immigrant women. Our objective was to assess breast, cervical, and colorectal cancer screening rates among immigrant women from Cambodia, Somalia, and Vietnam and explore screening barriers. Methods We measured screening rates by systematic chart review (N = 100) and qualitatively explored screening barriers via face-to-face questionnaire (N = 15) of women aged 50-75 from Cambodia, Somalia, and Vietnam attending a general medicine clinic (Portland, Maine, USA). Results Chart Review - Somali women were at higher risk of being unscreened for breast, cervical, and colorectal cancer compared with Cambodian and Vietnamese women. A longer period of US residency was associated with being screened for colorectal cancer. We observed a 7% (OR 1.07, 95% CI 1.01-1.13, p = 0.01) increase in the odds that a woman would undergo a fecal occult blood test for each additional year in the US, and a 39% increase in the odds of a woman being screened by colonoscopy or flexible sigmoidoscopy for every five years of additional US residence (OR 1.39, 95% CI 1.21-1.61, p = 0.02). We did not observe statistically significant relationships between odds of being screened by mammography, clinical breast exam or papanicolaou test according to years in the US. Questionnaire - We identified several barriers to breast, cervical, and colorectal cancer screening, including discomfort with exams conducted by male physicians. Discussion Somali women were less likely to be screened for breast, cervical, and colorectal cancer than Cambodian and Vietnamese women in this population, and uptake of colorectal cancer screening is associated with years of residency in this country. Future efforts to improve equity in cancer screening among immigrants may require both provider and community education.